Applying IFRS standards - Picker, Ruth (John Wiley & Sons, 2016)
Applying International Financial Reporting Standards, 3rd edition, has been thoroughly updated to reflect the varied and numerous developments in International Financial Reporting Standards (IFRSs). This book has been thoroughly updated to reflect the varied and numerous developments in International Financial Reporting Standards (IFRSs). The expert knowledge and authoritative explanations of the author team have resulted in the book being extensively referenced by both the accounting profession and academics in countries that have either adopted, or intend to adopt, international accounting standards. The continuing focus of the second edition of this book is on interpreting, analysing and illustrating the financial reporting requirements under IFRSs. Each chapter contains numerous illustrative examples that present and explain concepts to ensure that users gain a deep understanding of the reporting requirements and meet the knowledge expectations of the accounting profession.